Corrigendum to “Functional analysis of Trypanosoma brucei PUF1” - Luu, Van-Duc; Engert-Brems, Stefanie; Hoheisel, Jörg D.; Burchmore, Richard; Guilbride, D. Lys; Clayton, Christine (Molecular and biochemical parasitology, 2010)
In the above paper, the authors reported a wild-type RNAi phenotype for Trypanosoma brucei PUF9 in bloodstream-form cells. However, in a later study by the same group (Archer et al., 2009), a mild growth phenotype with morphological and cell-cycle perturbation was demonstrated in bloodstream-form cells derived from the previously analyzed RNAi cell line.
Online veröffentlicht am 19. September 2009
Gesehen am 20.04.2023